APPROXIMATION OF UNIVERSAL MAGNETIC CHARACTERISTIC FOR MODELLING ELECTRIC TRACTION MACHINES - Drubetskyi, A. Yu. (Science and Transport Progress, 2017)
Purpose. The scientific work is aimed to obtain an analytic expression describing universal magnetic characteristic and enabling to take into account the demagnetizing effect of the armature. On the basis of the universal magnetic characteristics one need to obtain universal expressions for inductive parameters of electric traction machines of direct and pulsating currents. Methodology. A universal magnetic characteristic (UMC) is the dependence of the relative units of the magnetic flux on the magnetomotive force (MMF) of the excitation winding. Since MMF was built for machines operating under load, therefore, in fact it is a dependency on the MMF and on the MMF of the armature reaction. For the calculation of electromechanical characteristics at constant excitation one can use one of the well-known expressions approximating the UMC. However, during modeling the electric traction engine operation in wide ranges of excitation change it is necessary the expression, in which there is a second variable in the form of MMF of the anchor reaction. Such an expression is also necessary to determine the inductive parameters of electric traction engine, to a large extent dependent on the current. The expression for the approximation of the UMC with two variables can be obtained by analyzing the magnetic field distribution in the air gap at the calculated pole arc. Findings. The author obtained expression for approximation of the UMC, which depends on two variables: MMF of excitation and MMF of armature reaction. For a particular mode of excitation weakening it is possible to convert the expression into the function of one variable, for example, the anchor current. Also, the MMF of excitation winding can be the argument. Originality. For the UMC approximation it was proposed a methodology that makes it possible to record into approximating expression the second variable in the form of the anchor reaction MMF. Practical value. Due to the presence of speed characteristic or saturation ratio of this electric traction engine, one can determine its inductive parameters in a particular operation mode or to obtain their dependencies on the winding currents for all modes of operation.